Dedifferentiation of Functional Brain Activation Associated With Greater Visual Discrimination Accuracy in Middle-Aged and Older Adults - Seider, Talia R.; Porges, Eric C.; Woods, Adam J.; Cohen, Ronald A. (Frontiers in Aging Neuroscience, 2021)
Neural dedifferentiation refers to an age-related phenomenon whereby brain functions that are localized to specific, distinct, and differentiated brain areas in young adults become less so as people reach more advanced age. Older adults tend to exhibit greater spread of cortical activation on fMRI during cognitive processing compared to younger adults, with evidence that this occurs during visuoperceptual processing. Some age-related functional changes are considered compensatory, but whether dedifferentiation is compensatory is not clearly understood. The current study assessed dedifferentiation and visual discrimination performance during simultaneous match-to-sample tasks from the Visual Assessment Battery (VAB) among 40 healthy middle-aged and older adults using fMRI. Task-relevant regions of interest (ROIs) were created in the dorsal stream for discrimination of spatial location, the ventral stream for shape, and an area encompassing V5 for velocity. Dedifferentiation, or less specificity in functional activation, was associated with greater discrimination accuracy and more years of education. Secondary analyses showed that reduced functional activation in task-relevant ROIs was associated with faster discrimination speed. Age was unassociated with functional activation. Results suggest that dedifferentiation is compensatory. Lack of age effects suggest that other factors beyond age, such as cognitive or brain reserve, may better predict performance when considering cognitive skills that are relatively stable as adults age, such as visual discrimination.